Exploring the association between childhood limiting long-term illness/disability and social disadvantage: Does social disadvantage precede or follow the onset of childhood limiting long-term illness/disability?. (13th September 2011) - Spencer, N*; Blackburn, C; Read, J
Abstract : Introduction: There is a lack of empirical evidence on the predictors and temporal ordering of factors associated with childhood limiting long-term illness/disability (LLTI/D). Objective: To examine the relationship between social disadvantage in earlier childhood and the onset of LLTI/D in later childhood in the UK Office for National Statistics (ONS) Longitudinal Study (ONS-LS). Methods: Children born between the 1981 and 1991 UK censuses who became ONS-LS members and were present at the 2001 census were identified. Data were extracted on those children who didn't have LLTI/D in 1991 but did in 2001 (index) and those who had no LLTI/D on either occasion (comparison). A social disadvantage index (SDI) was constructed. Logistic regression models were fitted on LLTI/D with the SDI as the independent variable of interest adjusted for age, gender, lone parenthood and ethnicity. Results: 60, 000+ children became ONS-LS members between the 1981 and 1991 and were present at the 1991 and 2001 censuses. 52, 438 in the index and comparison groups had complete data. In bivariate analyses, social disadvantage, age, gender and lone parenthood but not ethnicity were significantly associated with the onset of LLTI/D in the index group. After adjustment for confounding, the SDI showed a finely graded association with onset of LLTI/D in the index group (most disadvantaged Odds Ratio (OR) 2.12 (1.77, 2.54); disadvantaged in two domains OR 1.45 (1.20, 1.75); disadvantaged in one domain OR 1.14 (0.94, 1.40)). Conclusions: Social disadvantage in earlier childhood is a predisposing factor for the development of LLTI/D in later childhood and teenage years. Social disadvantage may be both cause and consequence of childhood LLTI/D.